2020
DOI: 10.1088/1757-899x/748/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Design and analysis of double wishbone suspension system

Abstract: Suspension system serves purpose of providing stability to vehicle which results improving comfortability of riding. It provides traction control and steering stability. This paper proposes a method for designing double wishbone suspension system for electric solar vehicle with damper to lower wishbone. Recent trends in suspension system have focused on improving innovations in ride quality and handling of vehicles. It maintains a viable spectrum of economic growth by reducing costs and increasing efficiency s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…The use of VAE consists of a material database and an FEM solver. Several papers that focus on designing a double wishbone suspension [5]- [8] were studied, the main aim of the authors were to create a design that is high strength as well as cost effective.…”
Section: Literature Studymentioning
confidence: 99%
“…The use of VAE consists of a material database and an FEM solver. Several papers that focus on designing a double wishbone suspension [5]- [8] were studied, the main aim of the authors were to create a design that is high strength as well as cost effective.…”
Section: Literature Studymentioning
confidence: 99%
“…layout and analysis of wishbones, dampers, bell crank, and push rod, which includes all layouts, calculations, and applications of various features in elements, led to the creation of the ideal design with a high level of safety and minimal component stress [16]. Analysis showed that AISI4130 is the best material for A-arm items, and that this pattern requires pipes with an outer diameter of 1 inch and a thickness of 2 mm [17]. determined the component geometry and material properties as well as the system loads [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Frictional energy 5. Bumper Force, sometimes referred to as vibration induced by the road, is the force that is applied to the A arm [17]. Force on knuckle hub in z-axis FHz…”
Section: Wheel Calculationsmentioning
confidence: 99%
“…One illustrative instance is the utilization of a double wishbone configuration for the front suspension of an automobile. In the event that the right front wheel experiences vertical upward movement as a result of encountering an impediment, the left front wheel will remain stationary in terms of vertical displacement, provided that no comparable obstacle is present on the left wheel [14].…”
Section: Introductionmentioning
confidence: 99%